Development of a quantitative polymerase chain reaction assay for detection of the aetiological agents of piscine lactococcosis. Issue 6 (20th March 2022) - Shahin, Khalid; Mukkatira, Kaveramma; Yazdi, Zeinab; Richey, Christine; Kwak, Kevin; Heckman, Taylor I.; Mohammed, Haitham H.; Ortega, Cesar; Avendaño‐Herrera, Ruben; Keleher, Bill; Hyatt, Michael W.; Drennan, John D.; et al.
Abstract: Piscine lactococcosis is an emergent bacterial disease that is associated with high economic losses in many farmed and wild aquatic species worldwide. Early and accurate detection of the causative agent of piscine lactococcosis is essential for management of the disease in fish farms. In this study, a TaqMan quantitative polymerase chain reaction (qPCR) targeting the 16S–23S rRNA internal transcribed spacer region was developed and validated. Validation of the qPCR was performed with DNA of previously typed L. petauri and L. garvieae recovered from different aquatic hosts from distinct geographical locations, closely related bacterial species and common pathogens in trout aquaculture. Further diagnostic sensitivity and specificity was investigated by screening of fish, water and faecal samples. The developed qPCR assay showed high specificity, sensitivity and accuracy in detection of L . petauri and L. garvieae with lack of signals from non‐target pathogens, and in screening of rainbow trout ( Oncorhynchus mykiss ) posterior kidney and environmental samples. The detection limit of the qPCR was four amplicon copies. Moreover, the sensitivity of the qPCR assay was not affected by presence of non‐target DNA from either fish or environmental samples. The robustness, specificity and sensitivity of the developed qPCR will facilitate fast and accurate diagnosis of piscine lactococcosis to establish appropriate control measures in fish farms and aquaria.